Sistem Informasi Penggajian Berbasis Web Menggunakan Metode Fuzzy Tsukamoto Untuk Menentukan Besaran Gaji Karyawan Di SDIT Qoshru Al Athfal - Putri Amalia; Lazulfa, Indana; Aries Dwi Indriyanti; Hadi Sucipto (Fakultas Teknologi Informasi, 2024)
SDIT Qoshru Al Athfal is an integrated Islamic-based elementary school (SD) in Jombang which has 12employees. The problem experienced so far in the payroll process is that the agency does not yet have acomputerized payroll information system that can be used to calculate employee salaries quickly, preciselyand accurately. This research aims to design and implement the fuzzy Tsukamoto method in a website-based payroll information system. This payroll information system is designed to be website-based usingthe PHP CodeIgniter programming language and MySQL as the database. The method used in thisresearch is Fuzzy Tsukamoto. The Fuzzy Tsukamoto method was chosen because of its fundamentalmathematics which is easy to learn. This method is used to determine the amount of employee salariesthrough three stages, namely Fuzzyfication, namely the formation of basic variables and fuzzy sets such aslength of service, education and attendance. Then Inference, namely determining fuzzy rules or rules basedon predetermined variables, and finally Defuzzyfication, namely calculating the amount of employee salaryobtained from membership degrees and fuzzy rules. The result of this research is a web-based payrollinformation system. This system can also print attendance reports, pay slips and fuzzy data reportsaccording to employee needs with 100% accuracy.Keywords: Fuzzy Tsukamoto, Pay Information System, Employee Pay.